Vertical Orientated Dion–Jacobson Quasi‐2D Perovskite Film with Improved Photovoltaic Performance and Stability. Issue 5 (23rd December 2019) - Li, Fengzhu; Zhang, Jie; Jo, SaeByeok; Qin, Minchao; Li, Zhen; Liu, Tiantian; Lu, Xinhui; Zhu, Zonglong; Jen, Alex K.‐Y.
Abstract: Dion–Jacobson (DJ) phase 2D layered perovskites with diammonium organic cations demonstrate improved stability over 3D perovskites under thermal/photo/moisture stresses. However, the power conversion efficiency (PCE) of DJ phase perovskite solar cells (PVSCs) is often limited by the poor charge transport across the perovskite layers due to the crystal growth direction that tends to be parallel to the substrate. Here, a simple and effective method is demonstrated by employing a NH4 SCN additive to facilitate the orientation of perovskite crystal growth to be perpendicular to the substrate. Also, the layer number distribution can be narrowed to around n = 3 and n = 4 with NH4 SCN addition. The device derived from the quasi‐2D DJ (BDA)(MA)4 Pb5 I16 perovskite film processed with NH4 SCN shows a PCE of 14.53%, which is among the highest values reported for 2D PVSCs prepared at room temperature. Moreover, the device retains 85% of its initial PCE after 900 h storage in ambient conditions with a humidity level of 50 ± 5%. These results demonstrate that this attractive approach will enable highly efficient and stable PVSCs to be made for renewable energy applications. Abstract : A simple and effective method to tune the vertical orientation of quasi‐2D perovskite crystals is realized with a NH4 SCN additive. This enhances the charge transports in Dion–Jacobson (DJ) layered 2D perovskites and improves the power conversion efficiency (PCE) to 14.53%, which is the highest PCE of quasi‐2D perovskites solar cells prepared at room temperature.